Bacterial Identification and Antibiotic Sensitivity Tests of COVID-19 Patients at ICU Wahidin Sudirohusodo Hospital - Ampulembang, Diana Tangdan; Handayani, Irda; Abdul Kadir, Nursin (Indonesian Association of Clinical Pathologist and Medical laboratory, 2025)
The use of antibiotics in COVID-19 pneumonia patients admitted to the ICU with various risk factors can increase the possibility of antibiotic resistance. Irrational antibiotic use during the pandemic is one of the causes of antibiotic resistance. This study aimed to describe bacterial identification and antibiotic resistance in pneumonia patients admitted to the COVID-19 and non-COVID-19 ICU Dr. Wahidin Sudirohusodo Hospital. This study was a descriptive observational study with a cross-sectional method. Data were collected from medical records from Dr. Wahidin Sudirohusodo Hospital for the period January 2020-December 2022. The population that met the inclusion criteria were pneumonia patients admitted to the COVID ICU and non-COVID ICU and had pneumonia thoracic photographs, positive culture results, and antibiotic sensitivity tests. A total of 532 patients diagnosed with COVID-19 and 53 non-COVID-19 were treated in the ICU. Samples that met the inclusion criteria were 77 subjects with COVID-19 with 87 culture specimens and 36 non-COVID-19 patients with 47 culture specimens. The most common types of bacteria were Gram-negative bacteria in the COVID-19 (70.1%) and non-COVID-19 (78.7%) groups, Acinetobacter baumannii were primarily found in non-COVID-19 (29.8%) and COVID-19 patients (14.9%). The most common sensitivity test result was MDR in the COVID-19 (65.5%) and non-COVID-19 (72.3%) groups. The most common antibiotic resistance in both groups were Cephalosporins, Carbapenems, and Fluoroquinolones against Acinetobacter baumannii. Antibiotics that remained sensitive to Acinetobacter baumannii were Amikacin and Gentamicin. Bacterial identification results of COVID-19 and non-COVID-19 patients showed dominance of Gram-negative bacteria. The antibiotic sensitivity test showed MDR as the most common result.